Biodegradation of azo dyes and dyes present in textile wastewaters using Bacillus sp. az28, obtained from industrial effluents - Suhag, Mahmudul Hassan; Haque, KM Anis Ul; Hossen, Md Zobaidul; Azad, Abul Kalam; Younus, Muhammad (Journal of Bangladesh Academy of Sciences, 2021)
The bacterial isolate Bacillus sp. AZ28, obtained from industrial effluent, demonstrates a great capacity to degrade various azo dyes (methyl orange (MO), magneson I (MI), novacron dark blue (NDB), and novacron red FN 3GF (NRF3)), and azo dye-containing textile effluent (TE). The degradation was evident by decolorization of dyes, and the decolorization efficiency of 84-95% was achieved within 14-72 h under optimum conditions, such as 37˚C, pH 7, inoculation size 8%, 1% glucose, and 1% beef extract. The extent of decolorization of individual dye was determined by UV–Vis spectroscopy, and products of biodegradation were analyzed by FTIR spectroscopy and TLC analyses. Chemical analysis showed that the COD and BOD values were significantly reduced after treatment. Thus, the biodegradation ability under mild conditions suggests that Bacillus sp. AZ28 has potential in textile effluent treatment. J. Bangladesh Acad. Sci. 45(1); 117-122: June 2021